Alex Delaware : Night Moves - Book 33 - Kellerman, Jonathan (New York : Ballantine Books, 2018)
"The #1 New York Times bestselling author and master of the psychological thriller makes all the right moves in this new novel of spellbinding suspense. Even with all his years of experience, LAPD homicide detective Milo Sturgis knows there are crimes his skill and savvy cannot solve alone. That's when he calls on brilliant psychologist Alex Delaware to read between the lines, where the darkest motives lurk. And if ever the good doctor's insight is needed, it's at the scene of a murder as baffling as it is brutal. There's no spilled blood, no evidence of a struggle, and, thanks to the victim's missing face and hands, no immediate means of identification. And no telling why the disfigured corpse of a stranger has appeared in an upscale L.A. family's home. Chet Corvin, his wife, and their two teenage children are certain the John Doe is unknown to them. And yet their cooperation seems oddly guarded. But even the Corvins' thin response is more than Milo and Alex can elicit from their creepy next-door neighbor--a notorious cartoonist with a warped sense of humor and a seriously antisocial attitude. As the investigation ensues, it becomes clear that this well-to-do suburban enclave has its share of curious eyes, suspicious minds, and loose lips. And as Milo tightens the screws on potential persons of interest--and Alex tries to breach the barriers that guard their deepest secrets--a strangling web of corrupted love, cold-blooded greed, and shattered trust is exposed. Though the grass may be greener on these privileged streets, there's enough dirt below the surface to bury a multitude of sins. Including the deadliest. Praise for Jonathan Kellerman "Jonathan Kellerman has mastered the art of lean, evocative prose [in] a series that grows stronger with each volume."--New York Journal of Books "Jonathan Kellerman's psychology skills and dark imagination are a potent literary mix."--Los Angeles Times "A master of the psychological thriller."--People "The combination of Alex Delaware [and] Milo Sturgis. makes for the most original whodunit duo since Watson and Holmes."--Forbes"--
"An affluent family returns home from Sunday dinner only to find the murdered and brutalized corpse of a total stranger in their house. This baffling, twisted tale tests Alex and Milo to their intellectual and emotional limits"--
Publishers Weekly
Library Journal Prepub Alert
Publishers Weekly Starred Reviews
Adult
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Police -- Fiction -- California; Psychologists -- Fiction; Murder -- Fiction -- Investigation; Suspense fiction; Mystery fiction